2017
DOI: 10.14694/edbk_180328
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive T-Cell Therapy for Solid Tumors

Abstract: OVERVIEW Chimeric antigen receptor (CAR) T-cell therapy is an innovative form of immunotherapy wherein autologous T cells are genetically modified to express chimeric receptors encoding an antigen-specific single-chain variable fragment and various costimulatory molecules. Upon administration, these modified T cells traffic to, and recognize, cancer cells in an HLA-independent manner. CAR T-cell therapy has shown remarkable success in the treatment of CD-19–expressing B-cell acute lymphocytic leukemia. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 118 publications
(137 reference statements)
0
21
0
Order By: Relevance
“…One of the main reasons for the poor clinical efficacy of CAR T cells in treating solid tumor is the lack of robust in vivo proliferation (34)(35)(36)(37). In this study, we demonstrated that knocking out TGFBR2 enables CAR T cells to survive and proliferate better in tumor xenograft mouse models, leading to significantly improved antitumor efficacy.…”
Section: Discussionmentioning
confidence: 71%
“…One of the main reasons for the poor clinical efficacy of CAR T cells in treating solid tumor is the lack of robust in vivo proliferation (34)(35)(36)(37). In this study, we demonstrated that knocking out TGFBR2 enables CAR T cells to survive and proliferate better in tumor xenograft mouse models, leading to significantly improved antitumor efficacy.…”
Section: Discussionmentioning
confidence: 71%
“…2 In particular, the number of clinical trials of chimeric antigen receptor T cells has dramatically increased in the recent decade. 3 The main goal of such immunotherapies is to enhance the activity of tumor-specific CD8 + T cells in order to achieve tumor eradication. However, in vitro activated CD8 + T cells often exhibit dysfunction, also known as "exhaustion," before achieving sufficient elimination of tumor cells, which restricts the therapeutic efficacy of cancer immunotherapies.…”
Section: Introductionmentioning
confidence: 99%
“…These two seem to be the culprits for the resistance mechanisms of CAR T-cell therapy in solid tumors. By changing the design of CAR T-cells incorporating co-stimulatory molecules, ligands, targeted therapies, or immunomodulatory agents can improve the clinical outcome [54]. Wang et al [55] suggest that targeting more than one antigen and building a dual-targeted CAR can overcome the risk of antigen escape relapse and diminish the effect of antigen heterogeneity.…”
Section: Car T-cell Therapy In Solid Tumorsmentioning
confidence: 99%